2016
DOI: 10.1093/phe/phw013
|View full text |Cite
|
Sign up to set email alerts
|

Towards a ‘Sociorelational’ Approach to Conceptualizing and Managing Addiction

Abstract: This article looks at how and why addiction should be understood as a 'sociorelational' (social and relational) disorder, and what this implies on a policy level in terms of the treatment and prevention of addiction. In light of scientific research, we argue that the neurobiological changes that underlie addiction are heavily influenced by sociorelational processes. We thereby advocate for a conceptual approach in which autonomy in addiction is a sociorelational concept, and social environments are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…There is controversy whether behavioral compulsions should be treated as addiction disorders or as an individual’s adaptive choices [73,101] that should be dealt with by accounting for socio-relational heterogeneities [72]. Weisel et al have previously suggested that screen addiction is not necessarily a problematic phenomenon (as it is commonly referred to in the literature), but a manifestation of the individual’s coping strategy, which should be channeled toward care [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is controversy whether behavioral compulsions should be treated as addiction disorders or as an individual’s adaptive choices [73,101] that should be dealt with by accounting for socio-relational heterogeneities [72]. Weisel et al have previously suggested that screen addiction is not necessarily a problematic phenomenon (as it is commonly referred to in the literature), but a manifestation of the individual’s coping strategy, which should be channeled toward care [24].…”
Section: Discussionmentioning
confidence: 99%
“…Life satisfaction related to external factors that include relationships at work and with friends and family, financial control, and work/leisure satisfaction. These findings underline the necessity of designing experiments that account for personal and social variants that account for population heterogeneities in media selectivity, resilience, and coping [72-74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this Research Topic, Human Connection as a Treatment for Addiction , is to bring together scholars from various fields to explore the question of whether intentionally increasing meaningful, caring interaction between people may reduce substance and/or non-substance related addictive behaviors. Previous research supports the role that social connection may play in the initiation and maintenance of addiction in both animals and humans (van der Eijk and Uusitalo, 2016 ; Christie, 2021 ).…”
mentioning
confidence: 59%
“…Addiction in general or the opioid-dependent kind in particular is, therefore, foundationally sociorelational. Eijk and Uusitalo (2016) recently argued that this perspective is crucial for developing more ethical treatment and prevention policies. In the context of siOAT research, a sociorelational lens nuances voluntary consent since its underlying idea of competence is mired in uncertainty that can only be specified on a case-by-case basis.…”
mentioning
confidence: 99%